A Critical Analysis of the Case-Law of the Bulgarian Constitutional Court Concerning Legislative Retroactivity - Mateeva, Ekaterina (Yearbook of the Law Department, 2021)
This study focuses on the concept of retroactive application of the new law within the meaning of established case-law of the Bulgarian Constitutional Court (the Court). It is emphasized upon the circumstance that the Bulgarian Constitution does not contain a general prohibition on attributing a retroactive effect of the law, in the absence of an explicit legislative guidance to the contrary (e. g. sec. 5, para 3 of the Constitution). The Court finds that the principle stating that laws should have prospective effect should be derived from the rule of law as a constitutional principle (art. 4, para 1 of the Constitution). The present study examines the cases in which the Court finds that the prohibition of the retroactive effect of the law is applicable in cases of retroactivity ‘stricto sensu’, where the trust in the stability of the legal system, legal certainty and acquired substantive rights are violated. According to the recent Court’s case-law the retroactive effect of the law is incompatible with the rule of law under specific conditions. The Court has adopted the view that according to the principle of protection of legitimate expectations, related to legal certainty, legislative changes that are sudden, unexpected and disproportionate to constitutional standards must not be allowed.